The fate of dosed copper to inhibit nitrification in chloraminated water distribution system - Zhan, Weixi (Curtin University, 2007)
Chloramine as a secondary disinfectant has been widely used by many water utilities around the world especially in a distribution system requiring a longer retention time such as the 600km long Goldfield water distribution system of Western Australia. Chloramine is selected mainly due to its better stability and low by-products over other disinfectants. However, it is reported that under nitrifying conditions, chloramine residual could drop dramatically. Consequently the required disinfectant concentration can not be maintained. Nitrification, microbial process, is known to be causing rapid depletion of the chloramine residual and enhancing the growth of heterotrophic bacteria. In preliminary studies conducted in Water Corporation, copper at concentrations of 0.25mg/L has been found to be effective against nitrifiers. A concentration of 0.25mg/L as copper is achieved by directly dosing into the main pipeline at the outlet of the Cunderdin reservoir. Nonetheless, the preferred copper concentration can not be maintained as gradual decrease of dissolved copper in bulk water has been encountered along the pipeline.This research aimed to investigate fate of copper in bulk water and distribution system. Three fundamental mechanisms leading to copper loss had been investigated: gravitational sedimentation, adsorption onto wall or biofilm and mineral ions induced aggregation. During investigation of these mechanisms, potential controlling factors (pH, alkalinity, DOC, mineral ions…etc) were brought into a series of experiments as variables. Hardly can free cupric ions or copper hydroxide particles exist in bulk water samples. It was found that major Cu-containing forms are inorganic and organic copper compounds. Solubility of inorganic copper compounds is in equilibrium with calcium carbonate buffered system while organic copper compounds are controlled by organic matters and dissolved organic carbon in drinking water. Minerals such as ferric/ferrous ions and calcium ions contained in the distribution system can aggregate various copper species in bulk water to form particles.Consequently, it can lead to sedimentation or deposition onto walls or sediments. Wall adsorption had been simulated using glass fibre (GF) filters in the laboratory. GF filters were found able to absorb various forms of dissolved copper and copper compounds, though further work needs to be done to investigate the real pipe surface adsorption and complete the adsorption model. Historical data from the field had been analysed. Combined with laboratory results, it shows that both adsorption and mineral ions induced aggregation are contributing to the loss of copper in the distribution system. However, to further quantify these two mechanisms respectively and build up a comprehensive model, more field data are needed and more laboratory work needs to be done. Copper with different forms will be brought into inhibition experiments in the next stage of research in order to find effective form(s) against nitrifying bacteria. Based on the current achievement on the fate of copper, an inhibition strategy is suggested at the end of this thesis.